2006
DOI: 10.1007/s10549-006-9315-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protein elongation factor eEF1A2 predicts favorable outcome in breast cancer

Abstract: Breast cancer is the most common malignancy among North American women. The identification of factors that predict outcome is key to individualized disease management and to our understanding of breast oncogenesis. We have analyzed mRNA expression of protein elongation factor eEF1A2 in two independent breast tumor populations of size n = 345 and n = 88, respectively. We find that eEF1A2 mRNA is expressed at a low level in normal breast epithelium but is detectably expressed in approximately 50-60% of primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 34 publications
3
63
1
2
Order By: Relevance
“…eEF1A2 protein is also detectable in the rat ovarian epithelial ROSE 199 cell line ( Figure 1a, right panel) (Adams and Auersperg, 1985). The eEF1A2 antibody used for this analysis recognizes an eEF1A2 epitope (KVERKEGNASGVSL-LEALDT) that is identical between the rat and the human eEF1A2 isoforms (Kulkarni et al, 2006). High expression level of eEF1A2 protein was detected in selected cell lines (Figure 1b).…”
Section: Eef1a2 Expression Induces Rearrangement Of the Actin Cytoskementioning
confidence: 99%
See 2 more Smart Citations
“…eEF1A2 protein is also detectable in the rat ovarian epithelial ROSE 199 cell line ( Figure 1a, right panel) (Adams and Auersperg, 1985). The eEF1A2 antibody used for this analysis recognizes an eEF1A2 epitope (KVERKEGNASGVSL-LEALDT) that is identical between the rat and the human eEF1A2 isoforms (Kulkarni et al, 2006). High expression level of eEF1A2 protein was detected in selected cell lines (Figure 1b).…”
Section: Eef1a2 Expression Induces Rearrangement Of the Actin Cytoskementioning
confidence: 99%
“…eEF1A2 is highly expressed in 30-60% of tumors of the ovary, breast and lung (Lee, 2003;Li et al, 2005;Tomlinson et al, 2005;Kulkarni et al, 2006). Wild-type eEF1A2 has transforming properties: it enhances focus formation, allows growth in soft agar and increases the tumorigenicity of mouse and human cells in nude mice (Anand et al, 2002).…”
Section: Eef1a2 Activates Akt and Actin Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent finding that PI4KIIIb is genetically amplified in a subset of primary human breast tumors points to a specific role for PI4KIIIb in breast cancer (7). We have also previously implicated PI4KIIIb in breast oncogenesis as the protein is bound and activated by the breast cancer oncogene eEF1A2, and its high expression disrupts in vitro threedimensional mammary epithelial morphogenesis (11)(12)(13)(14)(15). Supporting a role for PI4KIIIb in breast cancer development, we show here that PI4KIIIb protein levels are increased in approximately 20% of primary human breast tumors assayed, consistent with the idea that high PI4KIIIb expression plays a role in breast cancer neoplastic development.…”
Section: Discussionmentioning
confidence: 92%
“…At a functional level, we have previously shown that PI4KIIIb is likely to regulate breast epithelial morphogenesis because ectopic PI4KIIIb expression disrupts in vitro three-dimensional acinar development in MCF10A cells (11). We have also identified PI4KIIIb as a downstream effector of eukaryotic elongation factor 1 alpha 2 (eEF1A2), a transforming gene that is amplified and highly expressed in breast and ovarian cancer (12)(13)(14)(15). Finally, PI4KIIIb expression has also been shown to inhibit apoptosis in MDA-MB 231 cells (16).…”
Section: Introductionmentioning
confidence: 99%